Numerical Analysis of Thermal Environment in Deep Mining - Qi Li; Shuang You; HongGuang Ji; Huici Xu; Huan Wang (Shock and Vibration)
To analyze heat effect in deep metal mines, it is crucial to understand the temperature field distribution around the mine tunnel. In this paper, a numerical model of the random mineral composition of the rock body is established based on finite element software to analyze the influence of the internal composition of the surrounding rock on the temperature field, and a numerical simulation model based on COMSOL finite element software is established based on the two heat exchange modes of heat conduction and heat convection in the surrounding rock. The results show that the numerical simulation results of a typical numerical simulation model using a single material are lower than the real situation; increasing the tunnel length does not increase the heat exchange efficiency between the rock wall and the air; increasing the wind velocity has a limited impact on the temperature field; the wind temperature more directly affects the mining surface; and the effect of wet air on the temperature field of the surrounding rock has a more substantial variation.